Analysis and Invariant Properties of a Lattice Boltzmann Method (Advances in Applied Mathematics and Mechanics, 2021)
We investigate a two-relaxation-time (TRT) lattice Boltzmannalgorithm with the asymptotic analysis technique. The results areused to analyze invariance properties of the method. In particular,we focus on time dependent Stokes and Navier-Stokes problems.